Mountain hazards in the Kanchanjunga area, eastern Nepal: landslides developed on lateral moraines - Watanabe, Teiji; Nakamura, Naohiro; Khanal, Narendra R. (Journal of Nepal Geological Society, 2000)
We examined the distribution, morphological characteristics, timing of occurrence, and possible causes of the landslides developed on the lateral moraines of Kanchanjunga Himal.Such landslides were found at seven sites. The main possibilities of sliding cause were the unloading due to rapid deglaciation and melting of permafrost. The landslides on the Holocene lateral moraines of the Kanchanjunga Glacier began to occur after the Little Ice Age. This was explained by the following observations: (1) the debris now deposits after the Little Ice Age cover the morainic material displaced by sliding; (2) the landslide scarp continues along the side and front slopes of the Little Ice Age tributary moraine; and (3) the moraine material and trail on it have slid down at places. The deglaciation in the Holocene age, therefore, was not able to cause the landslides. The ground-temperature and BTS measurements, and seismic sounding indicate that the lower limit of the present permafrost exists between 4,850 and 4,890 m on the south-facing slope in the Nupchu Valley. The landslides on the lateral moraines of the Kanchanjunga Glacier (4,760-5,200 m) may be related to the melting of permafrost or ''relict ice'' in the moraines.